The Creation of Value-added on Wood Carving Handicraft in Luang Prabang city, Luang Prabang Province - kongsap, phouvang; CHANTHAVONE , Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study aims to investigate: the purchasing behavior of customers in Luang Prabang district and province, the perspectives of entrepreneurs and consumers who purchase goods to enhance the value of wood carving craft products in Luang Prabang district and province and Adding value to wood carving craft items that influences customers' decisions to buy in Luang Prabang district and province. employing interviews as a method to gather information from 3 merchants of wood carving craft products and 385 respondents' questionnaires. The frequency, percentage, average, standard deviation, and multiple regression equation. The study's findings revealed: Customer behavior in choosing to buy wood carving craft products as a gift or souvenir, ordering them from the store, and recognizing that information from online advertising media influences his decision to buy. Products that the customer may choose from include wood carving handicrafts for other people's daily lives, low-image elephant products, fish and gold fish products, high-image elephant products, and horse products. The product has the same features as before, but price is a deciding factor when making a purchase, so there's no need to mark the product with a purchase value of between 500,001 and 1,000,000 kip and require a cash payment. Entrepreneurs' thoughts on adding value to handcrafted wood-carving goods. Three Entrepreneurs believe that adding value to wood carving craft goods is important in six areas: designing the product, using wood as a raw material, branding, design, service, and production. Customers' perceptions of the entrepreneur's ability to create added value across six dimensions are influenced in part by the following factors: product quality; service quality; design and production; and modeling. Three factors creating additional value in terms of products, design, and production were involved in the manufacture of wood carving craft products that influence customers' purchase decisions.